The Impacts of Visual Effects on User Perception With a Virtual Human in Augmented Reality Conflict Situations - Kim, Hanseob; Lee, Myungho; Kim, Gerard J.; Hwang, Jae-In (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Virtual humans (VHs) in augmented reality (AR) can provide users an illusory sense of being together in the real space. However, such an illusion can easily break when the augmented VH conflicts (or is overlaid) with the real objects. Recent spatial understanding technology is starting to make physically plausible VHs in response to collisions, but there are still limitations (e.g., resolution, accuracy) and inevitable conflict situations (e.g., unexpected passer-by), especially in daily life. Moreover, depending on the situation, VH's plausible behavior to avoid collision may rather interfere with the original interaction with the users. In this paper, we investigate three such situations: (1) when VH appears in a room through a closed door, (2) when the VH's body overlaps with static real objects, and (3) when a real moving object passes through the VH. While we considered (2) as an avoidable situation where physically plausible behaviors of VHs might be required, (1) and (3) were considered as inevitable situations (e.g., VH appearing out of nowhere, or passer-by cannot be aware of a virtual being), and we may not present VH's plausible behaviors, so alternatives might be required. Thus, for each of these notable situations in AR, we tested different visual effects as presentation methods for physical conflicts between a VH and real objects. Our findings indicate that visual effects improve VH's social/co-presence and physicality depending on the situations and effect types as well as influence users' attention/social behaviors. We discuss the implications of our findings and future research directions.